Pendampingan Strategi Mengerjakan Soal TOEFL Bagi Mahasiswa Pendidikan Bahasa Inggris FKIP-UIR : Assistance Strategy for Taking TOEFL Questions for English Education Students FKIP-UIR - Andi Idayani; Betty Sailun; Mia Febriani (Pusat Riset dan Inovasi Nasional, 2022)
The implementation of this community service activity aims to increase the understanding of FKIP students at the Islamic University of Riau in working on TOEFL questions. This is very much needed by students as early as possible so that they can prepare themselves to compete in the world of work later after they graduate from college. The facts on the ground show that there are many job opportunities for those who have English proficiency both orally and in writing. Therefore, the service team sees the need for educators to equip students with the ability to work on TOEFL questions, so that later they will understand how to do it and get the maximum score according to the needs of the world of work. This service is carried out in the English laboratory of FKIP UIR. The mentoring participants were 25 final semester students of the English Education Study Program FKIP UIR. With this assistance, it is hoped that they will be motivated to study TOEFL and be able to prepare themselves to compete for jobs. This service activity received a positive response from all activity participants. They said that such activities could be carried out on an ongoing basis so that they would continue to receive guidance in studying the TOEFL. Furthermore, participants are motivated to continue to improve their ability to work on TOEFL questions in order to get better job opportunities for the future.